Trusting norms in normative multi-agent systems - Abdul Hamid N.H.; Ahmad M.S.; Ahmad A.; Mahmoud M.A.; Yusoff M.Z.M.; Mustapha A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Decision making; Life cycle; Open systems; Coordinating agents; Design time; norm adoption; norms' trust; Open MAS; Open multi-agent system; trust; Multi agent systems